On the Long Way of Hermeneutics - Kačerauskas, Tomas (Problemos, 2000)
The long way of hermeneutics (Ricoeur’s term) is investigated as a semantic, an aesthetic and a poetic reflection in the article. Ricoeur’s theory of symbol and polysemy is the semantic going round. Gadamer’s dimensions of playing, imitation and recognition in a piece of art is the aesthetic going round. The poetic going round links both Ricoeur and Gadamer. The author shows the double content of philosophical poetics. It is the creative direction and the tragedy of the subject. Furthermore, the author analyses Gadamer’s crossing of aesthetic and poetics. According to the author, Gadamer tries to give an ontological aspect to a piece of art. The art is tragic being. In this way a piece of art becomes a model of hermeneutics. In the same way it is possible to define philosophical poetics. Philosophical poetics and aesthetic cross each other. They do not coincide with each other. The author shows seven aspects of Gadamer’s philosophical poetics. It is 1) the unit of meaning and sound, 2) recognition of the self, 3) the horizon of understanding during the reading, 4) ontology, 5) has no progress and no errors, 6) it is a model of hermeneutics, 7) it includes the tragedy of the human being.